Cosmeceutical properties of phenolic acids and use of microencapsulation to ensure controlled release - Taofiq, Oludemi (2017)
Skin care formulations are designed to exert multifunctional benefits to the skin, promoting the interest on natural bioactive compounds as cosmeceutical ingredients. However, the utilization of such natural ingredients can present constraints related to their stability (e.g. against pH and temperature) being microencapsulation useful to overlap some of these limitations [1]. The present work describes the anti-inflammatory, anti-tyrosinase and antimicrobial activities of phydroxybenzoic, p-coumaric, protocatechuic and cinnamic acids. These compounds were microencapsulated using the atomization/coagulation method with sodium alginate coagulated with calcium chloride. The obtained microspheres were characterized in terms of morphology, particle size distribution, FTIR and encapsulation efficiency. Free and microencapsulated individual compounds were then incorporated into a semi-solid cosmetic base formulation. HPLC-DAD was used to check the presence of the compounds in the formulations. Considering anti-inflammatory activity, p-Coumaric acid presented the lowest EC50 value (152 ± 6 μg/mL) (NO production inhibition), followed by cinnamic acid (180 ± 14 μg/mL), which was also the most active in the anti-tyrosinase assay (EC50 = 310 ± 50 μg/mL). All tested compounds displayed antimicrobial activity against Gram positive and Gram negative bacteria. The microparticles showed spherical morphology, various sizes (20-260 μm) with little agglomeration and a unimodal and bimodal particle size distribution (number and volume, respectively). The encapsulation efficiency was above 50 % in all cases. After incorporation, free compounds still maintained some of its bioactive properties, while the encapsulated forms preserved the bioactivity showing a slow release profile of the compounds. Concluding, this encapsulation procedure provides a suitable alternative to prolong retention of bioactive compounds for subsequent release (sustained release).